Using Stereochemistry to Control Mechanical Properties in Thiol–Yne Click‐Hydrogels. (28th October 2021) - Macdougall, Laura J.; Pérez‐Madrigal, Maria M.; Shaw, Joshua E.; Worch, Joshua C.; Sammon, Christopher; Richardson, Stephen M.; Dove, Andrew P.
Abstract: The stereochemistry of polymers has a profound impact on their mechanical properties. While this has been observed in thermoplastics, studies on how stereochemistry affects the bulk properties of swollen networks, such as hydrogels, are limited. Typically, changing the stiffness of a hydrogel is achieved at the cost of changing another parameter, that in turn affects the physical properties of the material and ultimately influences the cellular response. Herein, we report that by manipulating the stereochemistry of a double bond, formed in situ during gelation, materials with diverse mechanical properties but comparable physical properties can be obtained. Click‐hydrogels that possess a high % trans content are stiffer than their high % cis analogues by almost a factor of 3. Human mesenchymal stem cells acted as a substrate stiffness cell reporter demonstrating the potential of these platforms to study mechanotransduction without the influence of other external factors. Abstract : Controlling the stereochemistry of double bonds that are formed in situ using the nucleophilic thiol–yne addition enables the synthesis of robust hydrogels with mechanical properties that relate to the double bond stereochemistry. This approach allows the synthesis of hydrogels in which the other chemical and hence physical parameters remain the same providing a platform from which to isolate mechanical properties to direct cell differentiation.